Human papillomavirus genotype prevalence in invasive penile cancers from a registry-based United States population - Hernandez, Brenda Y.; Goodman, Marc T.; Unger, Elizabeth; Steinau, Martin; Powers, Amy; Lynch, Charles F.; Cozen, Wendy; Saber, Maria S.; Peters, Edward S.; Wilkinson, Edward J.; Copeland, Glenn; Hopenhayn, Claudia; et al. (Frontiers in Oncology, 2014)
Background. Human papillomavirus (HPV) is estimated to play an etiologic role in 40%-50% of penile cancers worldwide. Estimates of HPV prevalence in U.S. penile cancer cases are limited. Methods. HPV DNA was evaluated in tumor tissue from 79 invasive penile cancer patients diagnosed in 1998-2005 within the catchment areas of 7 U.S. cancer registries. HPV was genotyped using PCR-based Linear Array and INNO-LiPA assays and compared by demographic, clinical, and pathologic characteristics and survival. Histological classification was also obtained by independent pathology review. Results. HPV DNA was present in 50 of 79 (63%) of invasive penile cancer cases. Sixteen viral genotypes were detected. HPV 16, found in 46% (36/79) of all cases (72% of HPV-positive cases) was the most prevalent genotype followed equally by HPV 18, 33, and 45, which each comprised 5% of all cases. Multiple genotypes were detected in 18% of viral positive cases. HPV prevalence did not significantly vary by age, race/ethnicity, population size of geographic region, cancer stage, histology, grade, penile subsite, or prior cancer history. Penile cases diagnosed in more recent years were more likely to be HPV positive. Overall survival did not significantly vary by HPV status. Conclusions. The relatively high prevalence of HPV in our study population provides limited evidence of a more prominent and, possibly, increasing role of infection in penile carcinogenesis in the U.S. compared to other parts of the world.